Pemisahan senyawa aspirin dari obat analgesik dengan Kromatografi Lapis Tipis (KLT) - Puri, Ananda Anggelita Aprina (Maliki Interdisciplinary Journal, 2023)
Thin Layer Chromatography (TLC) is a chemical separation method based on the distribution of the stationary and mobile phases, TLC is often used in the analysis of a compound. Aspirin is a compound with another name acetylsalicylic acid which functions as an analgesic, anti-inflammatory drug and others. The purpose of this study was to determine the level of aspirin in analgesic drugs (commercial) using the TLC method. The stationary phase used in the TLC plate was silica gel and the mobile phase was a mixture of distilled water, n-butanol and acetic acid in the correct ratio. The results of the Thin Layer Chromatography qualitative analysis test showed that in analgesic drugs (commercial) there is aspirin with an Rf value that is almost the same as standard aspirin, namely 0.82 and 0.83. The results of the quantitative analysis test from Thin Layer Chromatography (TLC)-densitometry showed that the level of aspirin contained in one (commercial) analgesic drug tablet was 0.96%.